Measuring Conditions Conducive to Knowledge Development - Adams, Nan B; DeVaney, Thomas; Sawyer, Susan G (The Journal of Technology, Learning and Assessment, 2009)
The design of virtual learning environments for post-secondary instruction is rapidly increasing among public and private universities. While the quantity of online courses over the past 10 years has exponentially increased, the quality of these courses has not. As universities increase their online teaching activities, real concern about the best design for these online learning opportunities underscores the need to create effective and responsive virtual learning environments. Adams (2007) developed the Recursive Model for Knowledge Development in Virtual Environments. The premise of this model is the belief that good teaching and engaged learning should not be determined by the use of certain instructional tools but by the guiding principal that learning is an active and recursive process, where knowledge must be contextualized to be relevant to the learner. To this purpose, this article describes the initial development in the ongoing process of designing a valid and reliable assessment tool, the Virtual Learning Environment Survey—VLES, for exploring the degree to which the Recursive Model for Knowledge Development relates to effective design of online learning environments. This student self-report survey will seek to provide guidance for the assessment of online learning environments through collection of student perceptions of teaching strategies, knowledge approach, and knowledge ownership in online classrooms.